INTERANNUAL VARIABILITY OF SEA ICE CONDITIONS IN SYOWA STATION SECTOR DEDUCED FROM DMSP SSM/I DATA - エノモト, ヒロユキ; ワラシナ, ヒデオ; サイトウ, タカシ; シライワ, タカユキ; ENOMOTO, Hiroyuki; WARASHINA, Hideo; SAITO, Takashi; SHIRAIWA, Takayuki (National Institute of Polar Research, 1996)
P(論文) This paper focuses on the interannual variability of sea-ice conditions in spring and summer in the vicinity of Syowa Station. Sea ice extent and concentration are discussed using DMSP SSM/I satellite passive microwave data. Persistent high ice concentration was observed in December in 1989 and 1993. In those years, sea ice was formed earlier in the autumn (April-May) and expanded rapidly in this initial stage. The sea ice concentrations were higher throughout the winter season in these years. Cold and calm weather conditions in autumn seem to be important in determining the following winter ice condition. departmental bulletin paper